PENGOLAHAN LIMBAH MIJEL MENJADI SABUN SEBAGAI PELUANG USAHA BERBASIS HOME INDUSTRY - Kurnianingsih, Retno; Budiningrum, Endah Wening; Arisman, Arisman; Pamungkas, Leo Dagdyo (LPPM Akademi Manajemen Administrasi Yogyakarta, 2024)
The problem of used cooking oil waste both from households and from home-based businesses and the lack of facilities for disposal (shelter) of used cooking oil are classic reasons for the community so it is interesting to carry out community service activities. On the other hand, the phenomenon of waste that has not been utilised optimally while if the waste is managed properly it can provide benefits and home business opportunities. Therefore, it is necessary to carry out activities including: 1) socialisation and education of waste from the household industry into useful and economically valuable products 2) using appropriate technology and local wisdom. 3) calculation of product costs requires a simple accounting system 4) product packaging and marketing Methods This service activity aims to socialise the benefits of used cooking oil or used cooking oil into washing soap. The method of service activities carried out is by counselling, training and practice and mentoring. This activity was carried out for PKK women in Tegalwaru Hamlet who are members of the UMKM Communication Forum Sayegan Sleman. The expected goals include being able to reuse used cooking oil or used cooking oil into laundry soap products with economic value in addition to fostering public awareness of environmental hygiene and health.